Cover Feature: A DNA‐Encoded FRET Biosensor for Visualizing the Tension across Paxillin in Living Cells upon Shear Stress (Anal. Sens. 1/2022). Issue 1 (3rd December 2021) - Shao, Shuai; Deng, Sha; Jiang, Qingyun; Zhang, Hangyu; Zhang, Zhengyao; Li, Na; Cong, Fengyu; Tiihonen, Timo; Liu, Bo
Abstract : The cover shows a DNA‐encoded biosensor based on a Fluorescence Resonance Energy Transfer (FRET) technique named PaxTS. The biosensor consists of an LD12 domain, an LIM1234 domain, a nano‐spring and a pair of fluorescent proteins to convert the tension across paxillin to FRET efficiency in living cells, indicating that there exists a force transmission pathway described as 'membrane‐cytoskeleton‐FAs' and involves paxillin upon mechanical force. More information can be found in the Full Paper by Bo Liu and co‐workers .